Histopatologija in patogeneza glomerulonefritisa - Ferluga, Dušan (Medicinski razgledi, 2005)
The majority of primary glomerulonephritides is mediated by the deposition of circulating or in situ formed immune complexes, which may be confirmed by immunofluorescence finding of glomerular granular immune deposits. Their composition and electron microscopically defined localization identify variousforms of immune complex glomerulonephritides with different courses andprognoses. Acute postinfectious glomerulonephritis is endocapillary proliferative glomerulonephritis characterized by subepithelial hump-like deposits. The most frequent from of primary glomerulonephritis is IgA glomerulonephritis, which tends to be focal or irregular diffuse mesangial proliferative glomerulonephritis with dominant IgA deposits in the mesangium. Mesangiocapillary proliferative (membranoproliferative)glomerulonephritis is characterized by double contours of the glomerular basement membrane and subendothelial immune deposits. Mesangiocapillary proliferative (membranoproliferative) glomerulonephritis with intramembranous dense depositsand still unclear etiopathogenesis has a similarly unfavourable prognosis. Crescentic extracapillary proliferative glomerulonephritis is the most severe form of glomerulonephritis with a rapidly progressive clinical course. Its development is a consequence of glomerular capillary necrosis and fibrin exudation. It may represent an unfavourable variant of immune complex proliferative glomerulonephritides. In 1-2% it is mediated by anti-glomerular basement membrane antibodies and is characterized by linear glomerular immune deposits. In 5-7% of cases, extracapillary crescentic glomerulonephritis is pauci-immune and is associated with antineutrophil cytoplasmic antibodies. (Abstract trunacted at 2000 characters)
Keywords: Glomerulonephritis; Glomerulonephritis, Membranoproliferative; Glomerulonephritis, Iga; Etiology; Avtoprotitelesa; Pathology; Classification; Glomerulonefritis; Glomerulonefritis membranoproliferativni; Immune Complex Diseases; Imunski kompleks, bolezni; Autoantibodies; Antibodies, Antineutrophil Cytoplasmic; Protitelesa antinevtrofilna, citoplazemska; Glomerulonefritis IGAMESH/slv; Glomerulosclerosis, Focal; Glomerulonephritis, Membranous; Glomerulonefritis membranski; Glomeruloskleroza fokalna; ledvične bolezni; vnetja; patologija; histopatologija